Oxford international primary English student book grade 5 - Barber, Alison (Karachi : Oxford university press, 2022)
The Oxford International Primary English Student Book Grade 5, Second Edition is designed to further enhance students' English language skills with more complex themes and activities, building on the skills learned in earlier grades. It focuses on reading, writing, speaking, and listening, encouraging students to apply their language knowledge in real-world contexts.
Keywords: English : Textbook